2021
DOI: 10.1038/s41598-021-95128-x
|View full text |Cite
|
Sign up to set email alerts
|

A stacking ensemble deep learning approach to cancer type classification based on TCGA data

Abstract: Cancer tumor classification based on morphological characteristics alone has been shown to have serious limitations. Breast, lung, colorectal, thyroid, and ovarian are the most commonly diagnosed cancers among women. Precise classification of cancers into their types is considered a vital problem for cancer diagnosis and therapy. In this paper, we proposed a stacking ensemble deep learning model based on one-dimensional convolutional neural network (1D-CNN) to perform a multi-class classification on the five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 52 publications
0
49
1
Order By: Relevance
“…At the same time, the selection of the distribution will be carried out against the goodness of fit, taking as reference the lowest NlogL. In this same stage, two generalised neural models with deep-learning structures, which had been widely used for pattern identification and classification, were used to validate the model: a stochastic neural model with a stacked deep learning structure (SSDL) [14] and a convolutional deep-learning neural network (CDLM) with stochastic computing [13]. In the validation stage, LG-HDLM was expected to yield probability distributions with extended S-GAPs, and performance indices higher than 75% on average (ELM-750 un.)…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the selection of the distribution will be carried out against the goodness of fit, taking as reference the lowest NlogL. In this same stage, two generalised neural models with deep-learning structures, which had been widely used for pattern identification and classification, were used to validate the model: a stochastic neural model with a stacked deep learning structure (SSDL) [14] and a convolutional deep-learning neural network (CDLM) with stochastic computing [13]. In the validation stage, LG-HDLM was expected to yield probability distributions with extended S-GAPs, and performance indices higher than 75% on average (ELM-750 un.)…”
Section: Experimental Validationmentioning
confidence: 99%
“…This evaluation identifies the reflectance band (Spectral image) or vegetation index (VI) that allows better identification of MCOPs by LW-affectation. In the first phase within a second stage, the LG-HDLM was evaluated against the reconstruction of the loss structure defined by Scenario 1 and was validated against two generalised deep-learning models commonly used for pattern classification and labelling: a deep-learning model with Stochastic stacked structure (SSDL) [13], and a deep-learning model with convolutional structure (CDLM) [14]. In a second phase within the same stage, the LG-HDLM (Substructure 2) was evaluated against three temporal risk scenarios showing the evolution of LW in a study zone for a period of 6 months before reference Scenario (Scenario 2-month 0, Scenario 2.1-month 1, Scenario 2.2-month 2).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al 5 used several machine learning algorithms to study lung adenocarcinoma and lung squamous cell cancer and identified 13 top genes. Mohammed et al 6 used least absolute shrinkage and selection operator (LASSO) as feature selection method to learn cancer type classification based on TCGA data. Chen and Dhahbi 7 applied overlapping feature selection methods for cancer classification and biomarker identification.…”
Section: Introductionmentioning
confidence: 99%
“…This may be credited to the availability of knowledgeable individuals with sufficient skills to perform optimal data pre-processing, model selection, tuning, validation, and software deployment. However, many novel AI platforms that are being developed by African institutions affiliates may be employing open-source databases comprised of patients from other populations [ 33 - 37 ]. This alludes to the unavailability of clinical, imaging, pathologic, and molecular data from cancer patients, especially in electronic formats, within many parts of the regions.…”
Section: Implementation and Potential Refinements For Cancer-based Ar...mentioning
confidence: 99%